2015
DOI: 10.1093/jnci/djv371
|View full text |Cite
|
Sign up to set email alerts
|

Choline Kinase Alpha as an Androgen Receptor Chaperone and Prostate Cancer Therapeutic Target

Abstract: Background:The androgen receptor (AR) is a major drug target in prostate cancer (PCa). We profiled the AR-regulated kinome to identify clinically relevant and druggable effectors of AR signaling.Methods:Using genome-wide approaches, we interrogated all AR regulated kinases. Among these, choline kinase alpha (CHKA) expression was evaluated in benign (n = 195), prostatic intraepithelial neoplasia (PIN) (n = 153) and prostate cancer (PCa) lesions (n = 359). We interrogated how CHKA regulates AR signaling using bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
60
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 61 publications
1
60
1
Order By: Relevance
“…Examples include arrest‐defective protein 1 (ARD1), an oncoprotein that enhances dissociation of the ligand‐bound AR from HSP90 by acetylation of the K618 residue of AR, leading to PCa tumor growth . Recently, a novel chaperone of AR, choline kinase‐α (CHKA) is shown to be upregulated in PCa and bind directly to the AR LBD, a region where HSPs bind . Interestingly, inactivation of CHKA results in downregulation of AR protein levels.…”
Section: Molecular Chaperones Stabilize the Armentioning
confidence: 99%
See 3 more Smart Citations
“…Examples include arrest‐defective protein 1 (ARD1), an oncoprotein that enhances dissociation of the ligand‐bound AR from HSP90 by acetylation of the K618 residue of AR, leading to PCa tumor growth . Recently, a novel chaperone of AR, choline kinase‐α (CHKA) is shown to be upregulated in PCa and bind directly to the AR LBD, a region where HSPs bind . Interestingly, inactivation of CHKA results in downregulation of AR protein levels.…”
Section: Molecular Chaperones Stabilize the Armentioning
confidence: 99%
“…Interestingly, inactivation of CHKA results in downregulation of AR protein levels. Accordingly, inactivation of CHKA reduced tumor growth of CRPC in xenograft mice indicating that the chaperone function of CHKA and its interaction with AR renders CHKA an interesting drug target to downregulate AR protein levels . The co‐chaperone folliculin‐interacting proteins (FNIPs) positively regulate the HSP90 chaperone cycle and are highly expressed in tumors .…”
Section: Molecular Chaperones Stabilize the Armentioning
confidence: 99%
See 2 more Smart Citations
“…We showed that choline kinase a (CHKA) is a chaperone for the AR, promoting its stability and function. 6 This is the first report demonstrating that kinases can act as chaperones. During our studies we also identified 49 androgen-regulated kinases, of which 25 were upregulated and 24 were downregulated.…”
mentioning
confidence: 95%